2016
DOI: 10.1177/1069072716639689
|View full text |Cite
|
Sign up to set email alerts
|

Linking Job Design to Subjective Career Success

Abstract: We tested a predictive model based on self-determination theory (SDT) to demonstrate how job design choices contribute to subjective career success. Data collected at Time 1 demonstrated that the job characteristics of autonomy support and competence support had direct and interactive effects on employees' need satisfaction. Need satisfaction at Time 1 mediated the relationship between autonomy support and self-determined work motivation at Time 2. Work motivation, in turn, mediated the relationships between n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 78 publications
4
38
0
Order By: Relevance
“…The present study addressed career satisfaction as a psychological mechanism that helps explain how basic psychological needs satisfaction relates to career commitment of nurses. Consistent with the study prediction and in line with previous studies (e.g., Dahling & Lauricella, ; Gagné et al., ), the results show that nurses who are able to fulfil their basic psychological needs are likely to be satisfied with their careers. The finding that basic psychological needs satisfaction is significantly related to career commitment of nurses suggests that nurses whose basic psychological needs are met are likely to be more committed to their careers.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study addressed career satisfaction as a psychological mechanism that helps explain how basic psychological needs satisfaction relates to career commitment of nurses. Consistent with the study prediction and in line with previous studies (e.g., Dahling & Lauricella, ; Gagné et al., ), the results show that nurses who are able to fulfil their basic psychological needs are likely to be satisfied with their careers. The finding that basic psychological needs satisfaction is significantly related to career commitment of nurses suggests that nurses whose basic psychological needs are met are likely to be more committed to their careers.…”
Section: Discussionsupporting
confidence: 92%
“…Career commitment has to do with the development of self‐generated career‐related goals, and identification with and involvement in the goals in question (Colarelli & Bishop, ). Researchers have also recognized the importance of the subjective feeling of career success for the individual worker and the organization (Dahling & Luricella, ). Individuals with positive career beliefs have been found to have higher work life balance (Sturges, ), cope better with job challenges (Eddleston, ), and less likely to quit their jobs (Simon, Müller, & Hasselhorn, ).…”
mentioning
confidence: 99%
“…The results of these surveys showed that the ability of administrators to properly plan and management career programs had enhanced employees' proactive behavior (Searle, 2011;Brandt, 2012;Marinova et al, 2015;Van Der Zee, 2016), and promotion opportunities (Stumpf, 2007;Ali & Zia-ur-Rehman, 2014;Dahling & Lauricella, 2016: Zhang, 2014.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies about effective career management highlight that the ability of administrators to appropriately design and manage career programs may have a significant impact on career outcomes, especially proactive behavior (Marinova, Peng, Lorinkova, Dyne, & Chiaburu, 2015;Van Der Zee, 2016) and promotion opportunity (Zhang, 2014;Ali & Zia-ur-Rehman, 2014;Dahling & Lauricella, 2016). In a career management perspective, proactive behavior is generally defined as employees have different characters such self-directed and future oriented behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation